2022
DOI: 10.3847/1538-4357/ac91d3
|View full text |Cite
|
Sign up to set email alerts
|

Suzaku Observations of the Cluster Outskirts and Intercluster Filament in the Triple Merger Cluster A98

Abstract: We present Suzaku observations of the Abell 98 (A98) triple galaxy cluster system and the purported intercluster filament. The three subclusters are expected to lie along a large-scale cosmic filament. With partial azimuthal coverage of the northernmost cluster, we find that the inferred entropy profile of this relatively low-mass cluster (kT ≈ 2.8 keV) adheres to expectations from models of self-similar pure gravitational collapse in the region of the virial radius. There is evidence of extended structure bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Figure 1 shows a slightly smoothed image of A98N (northern subcluster) and A98S (central subcluster) in the 0.5-2 keV band, obtained after co-adding all 10 observations and by applying the correction for exposure nonuniformity. As reported by earlier studies, the cluster is an early-stage merger, with the merger axis likely aligned along a local north-south (N-S) large-scale filament connecting A98N and A98S (e.g., Paterno-Mahler et al 2014;Alvarez et al 2022;Sarkar et al 2022).…”
Section: Imaging Analysissupporting
confidence: 53%
See 2 more Smart Citations
“…Figure 1 shows a slightly smoothed image of A98N (northern subcluster) and A98S (central subcluster) in the 0.5-2 keV band, obtained after co-adding all 10 observations and by applying the correction for exposure nonuniformity. As reported by earlier studies, the cluster is an early-stage merger, with the merger axis likely aligned along a local north-south (N-S) large-scale filament connecting A98N and A98S (e.g., Paterno-Mahler et al 2014;Alvarez et al 2022;Sarkar et al 2022).…”
Section: Imaging Analysissupporting
confidence: 53%
“…(e.g., Alvarez et al 2022;Sarkar et al 2022). Alvarez et al (2022) also reported a filament extending to the north beyond A98N, indicating A98N and A98S lie along a large-scale cosmic filament. In this work, we focus on the northern and central subclusters.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 1 shows a slightly smoothed image of A98N (northern sub-cluster) and A98S (central sub-cluster) in the 0.5-2 keV band, obtained after co-adding all ten observations and by applying the correction for exposure non-uniformity. As reported by earlier studies, the cluster is an early-stage merger, with the merger axis likely aligned along a local N-S large-scale filament connecting A98N and A98S (e.g., Paterno-Mahler et al 2014;Alvarez et al 2022;Sarkar et al 2022).…”
Section: Imaging Analysismentioning
confidence: 63%
“…Previous studies have reported a shock front associated with the northern sub-cluster and a filament connecting the northern and central sub-clusters. (e.g., Alvarez et al 2022;Sarkar et al 2022). Alvarez et al (2022) also reported a filament extending to the north beyond A98N, indicating A98N and A98S lie along a large-scale cosmic filament.…”
mentioning
confidence: 99%